Kulturní komunikace města Písek v letech 2011-2012 - Hesounová, Martina (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2013)
The thesis titled "Cultural communication of the Písek city in years 2010 - 2011" deals with the Písek city as a product on market and also deals with communication activities which were presented by the city in years 2010 - 2011. The aim of this dissertation is to give a comprehensive picture of these activities and the position of the Písek city in tourism in South Bohemia region. The thesis is divided in five main chapters including the conclusion. At first this thesis deals with a theoretical part where the general information is described. In the first chapters it analyses history, cultural heritage, celebrities, cultural events and interesting places. Then there is a chapter that focuses on the marketing part, promotion of the city. How the city tries to profile in its region and which communication channels uses. The third chapter of this thesis evaluates the status of marketing communication in selected year 2010 - 2011 and it also compares this status with the contemporary one from the year 2011 until now. In this part is also used the SWOT analysis which helps us to determinate the strengths, weaknesses, opportunities and possible threats of the city. A part of this chapter is also a qualitative research that was made among Písek inhabitants. The last chapter discusses the practical part...
Keywords: rozbor; komunikace města; SWOT analýza; marketingová komunikace; solution; analysis; řešení; marketing communication; Písek; communication of the city; SWOT analysis